Evaluation of two different doses of butorphanol-medetomidine-midazolam for anaesthesia in free-ranging versus captive black-footed cats (Felis nigripes) - Meyer, Leith Carl Rodney (University of Pretoria, 2016)
Mini Dissertation (MSc)--University of Pretoria, 2016.